2023
DOI: 10.2147/jpr.s415111
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Attenuates Neuropathic Pain in a Rat Model of Cervical Spondylotic Radiculopathy: Involvement of Spinal Cord Synaptic Plasticity

Abstract: Purpose Cervical spondylotic radiculopathy (CSR) is a common neurologic condition that causes chronic neck pain and motor functions, with neuropathic pain (NP) being the primary symptom. Although it has been established that electroacupuncture (EA) can yield an analgesic effect in clinics and synaptic plasticity plays a critical role in the development and maintenance of NP, the underlying mechanisms have not been fully elucidated. In this study, we explored the potential mechanisms underlying EA’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…It’s established that chronic pain can stem from the increased sensitivity of peripheral nociceptors in the spinal cord, coupled with persistent synaptic plasticity, highlighting the central role of synaptic changes in pain perception ( Bliss et al, 2016 ). Research by Yang P. et al (2023) in a rat model has demonstrated that electroacupuncture (EA) can mitigate the spinal cord compression (SCC)-induced upregulation of synaptic proteins, including α, 1, and 2, post-synaptic density protein 95 (PSD-95), and growth-associated protein 43 (GAP-43) within the spinal cord, suggesting EA’s capability to alter synaptic ultrastructure affected by CSR, thereby influencing the synaptic structure and functional plasticity to exert analgesic effects. Moreover, a study by Su J. et al (2023) revealed that EA effectively decreases the expression of pain-associated factor c-fos and the post-synaptic membrane protein neurontin 2 by inhibiting the expression of brain-derived neurotrophic factor (BDNF), phosphorylated tyrosine kinase B (P-TrkB), calmodulin-dependent protein kinase II (CAMKII), and phosphorylated response element binding protein (P-CREB) at spinal cord synapses.…”
Section: Acupuncture Exerts Analgesic Effects By Regulating the Plast...mentioning
confidence: 99%
“…It’s established that chronic pain can stem from the increased sensitivity of peripheral nociceptors in the spinal cord, coupled with persistent synaptic plasticity, highlighting the central role of synaptic changes in pain perception ( Bliss et al, 2016 ). Research by Yang P. et al (2023) in a rat model has demonstrated that electroacupuncture (EA) can mitigate the spinal cord compression (SCC)-induced upregulation of synaptic proteins, including α, 1, and 2, post-synaptic density protein 95 (PSD-95), and growth-associated protein 43 (GAP-43) within the spinal cord, suggesting EA’s capability to alter synaptic ultrastructure affected by CSR, thereby influencing the synaptic structure and functional plasticity to exert analgesic effects. Moreover, a study by Su J. et al (2023) revealed that EA effectively decreases the expression of pain-associated factor c-fos and the post-synaptic membrane protein neurontin 2 by inhibiting the expression of brain-derived neurotrophic factor (BDNF), phosphorylated tyrosine kinase B (P-TrkB), calmodulin-dependent protein kinase II (CAMKII), and phosphorylated response element binding protein (P-CREB) at spinal cord synapses.…”
Section: Acupuncture Exerts Analgesic Effects By Regulating the Plast...mentioning
confidence: 99%